School Risk and Protective Factors of Suicide: A Cultural Model of Suicide Risk and Protective Factors in Schools. Issue 3 (3rd June 2022) - Marraccini, Marisa E.; Griffin, Dana; O'Neill, J. Conor; Martinez, Robert R.; Chin, Andrew J.; Toole, Emily N.; Grapin, Sally L.; Naser, Shereen C.
Abstract: There are known cultural variations in correlates of and symptoms related to suicide-related thoughts and behaviors; however, the majority of research that informs suicide prevention in school systems has focused on research based on Euro-American/White students. By exploring school-related risk and protective factors in ethnic-racial minoritized students, we expand existing multicultural models of suicide prevention for school settings. Specifically, this systematic literature review identified 33 studies conducted with American Indian and Alaskan Native, Hispanic and Latinx, Black and African American, and Asian American and Pacific Islander students. Findings underscore the importance of building relationships with the school community and fostering a sense of safety for students, the need to approach school-based suicide prevention and intervention with cultural considerations, and the importance of connecting students and families with providers in culturally sensitive and informed ways. Taken together, schools need to build school–family–community partnerships that promote culturally sensitive approaches to suicide prevention. Impact Statement Findings from this review underscore the importance of strengthening school relationships, fostering a sense of safety and trust, and eradicating bullying for preventing suicide in ethnic-racial minoritized students. By expanding on previous theories of multicultural suicide prevention, we call for the implementation of culturally sensitive risk assessments and suicide prevention programs in school settings that are built from partnerships with families and communities.